Pengaruh Kualitas Produk dan Kualitas Pelayanan terhadap Kepuasan Pelanggan di PT Nusa Kharisma Raya - Iqbal Romadoni; Dedi Supiyadi; Erna Herlinawati (Jurnal Bisnis, Manajemen, dan Ekonomi, 2026)
This study examines the effects of product and service quality on customer satisfaction at PT Nusa Kharisma Raya, a medical device distributor serving institutional customers, including hospitals, clinics, laboratories, and pharmacies. A quantitative approach with a causal-associative design was employed. The study involved 100 respondents selected through purposive sampling based on their experience in purchasing, receiving, using, or evaluating the company’s medical device products. Data were collected using a 35-item questionnaire, measured on a five-point Likert scale. Product quality was measured through performance, features, reliability, durability, conformance, aesthetics, and perceived quality, while service quality was assessed through tangible, reliability, responsiveness, assurance, and empathy. Data were analyzed using descriptive statistics, validity and reliability testing, classical assumption testing, and multiple linear regression analysis. Service quality also has a positive and significant effect and shows a stronger contribution than product quality. Simultaneously, product quality and service quality significantly affect customer satisfaction and explain 57.4% of its variance. These findings confirm that customer satisfaction in medical device distribution depends not only on product conformity, reliability, and quality consistency, but also on delivery accuracy, employee responsiveness, communication, and complaint handling. The company should therefore integrate product quality control with contin